Mandibular morphology of the Mongoloid race in Medan according to age groups - Maria Sitanggang; Trelia Boel (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: The mandible constitutes part of the craniofacial bone that plays an important role in determining an individual’s facial profile. The mandible grows and develops throughout life from the prenatal phase up to old age when it becomes and edentulous. Changes in the mandible can be measured using radiographs. These establish several parameters of mandibular morphology, including: ramus height, condylion height, body length, condylion angle, symphysis height, symphysis width and symphysis angle. Purpose: This study aimed to determine differences in the mandibular morphology of members of the mongoloid racial group in Medan according to age as measured by cephalometric radiography. Methods: This investigation constituted analytical research using cross-sectional study with a total sample of 150 individuals divided according to age: group 1 (aged 4-12 years), group 2 (aged 13-24 years, group 3 (aged 25-34 years), group 4 (aged 35-60 years) and group of 5 (aged > 60 years). The parameters were computerized by means of a digital cephalometric radiograph, the resulting data being analized with Oneway ANOVA and LSD. Results: The mean value of the highest to the lowest ramus height, and symphysis height from the five age groups, sequentially, were in group 3, group 4, group 5, group 2, and group 1. The mean value from the highest to the lowest of body length, condylion height, condylion angle, and symphysis width, sequentially, were in group 3, group 4, group 2, group 5, and group 1. The mean value from the highest to the lowest of symphysis angle, sequentially, were in group 1, group 3, group 4, group 2, and  group 5. Conclusion: The mandibular morphology of each age group differs in Mongoloid races in Medan based on lateral cephalometric radiography in which changes are may be affected by the state of teeth and age.